ONLINE LEARNING PLATFORMS AND THEIR EFFECTIVENESS IN TEACHING ENGLISH GRAMMAR - Ostonova Charos Zubaydullayevna (The latest news and research in education, 2025)
Online learning platforms have become an integral part of modern language education, accelerating innovation in pedagogy and reshaping how English grammar is taught and learned. This research article investigates the effectiveness of such platforms in grammar instruction, drawing on theoretical models, recent empirical findings, and comparative insights from traditional classroom environments. The study identifies key affordances of digital platforms, including multimodality, adaptive learning algorithms, instant feedback systems, and autonomous learning mechanisms. The analysis concludes that online learning platforms significantly improve grammatical accuracy and learner engagement, though their effectiveness is influenced by platform design, learner motivation, and instructional integration.